How to prepare for the gre test - Green, Sharon Weiner; Ph.D., Ira Wolf ([S.l.] : Barron's Educational Series, 2003)
Updated to reflect the most recent Graduate Record Exams, this manual presents six full-length model tests with answers and explanations. It also offers intensive subject review in all test topics, which include antonym questions, analogy questions, sentence completion, reading comprehension, vocabulary, analytical writing, quantitative comparison, data interpretation, and mathematics. The all-important vocabulary review contains both a GRE high-frequency word list and a 3,500 master word list with definitions.